A Review of Leaf-mining Insects and Control Options for their Management, with Special Reference to Holocacista capensis (Lepidoptera: Heliozelidae) in Vineyards in South Africa - Steyn, L.A.I.; Geertsema, H.; Malan, A.P.; Addison, P. (South African Journal of Enology and Viticulture, 2020)
A leaf-mining pest occurring on commercial varieties of Vitis vinifera in South Africa was investigated due to the presence of cocoons on fruit. The leaf miner, Holocacista capensis, was reported on grapevines in 2012. Since its discovery on commercial grape varieties, control strategies have consisted solely of insecticide applications. Despite the fact that the leaf-mining habit is taxonomically diverse and considered ancient, little is generally known of leaf-mining larvae. A review was conducted in order to better understand the leaf-mining strategy and amalgamate the current knowledge of other leaf-mining insects. The general evolutionary history within the full complement of taxa that display the leaf-mining habit is discussed. The review focuses on lepidopteran leaf-mining pests and discloses the known information associated with the first report and the impact of H. capensis in the Western Cape, South Africa. As no control methods have been identified for H. capensis in vineyards, various chemical, biological and cultural control strategies adopted for other leaf-mining pests were investigated. Control options, including the use of entomopathogenic nematodes (EPNs), parasitoids, physical and cultural control measures, were considered and are discussed. Alternate control methods are pertinent for the grape-growing industry to avoid the development of the insecticide resistance that is common amongst leaf miners. This review aims to consolidate the available literature and therefore aid in the development of an integrated pest management strategy to effectively control H. capensis in infested vineyards in South Africa.